Computational Study of Turbulence and Recirculation Effects in Turbine Blade Cooling Channels (Global Journals of Research in Engineering, 2024)
This study introduces a two-dimensional computational model for the cooling passages in turbine blades Turbulators are installed on both sides of the duct to enhance turbulence and improve heat transfer efficiency The objective of this research is to analyze rectangular turbulators by examining the velocity pressure and turbulence before and after the turbulators The findings reveal that recirculation zones diminish following the first two turbulators but increase behind the final turbulator upstream of the U-turn Significant recirculation occurs on the upper and outer sides of the bend High-velocity regions are observed on the inner side of the bend and after the first lower turbulator downstream of the U-turn
Keywords: flow; turbine; blade; cooling; passage; turbulence modeling; gas turbine